Positive C4d Immunostaining of Placental Villous Syncytiotrophoblasts Supports Host-Versus-Graft Rejection in Villitis of Unknown Etiology. (January 2013) - Rudzinski, Erin; Gilroy, Meghan; Newbill, Colin; Morgan, Terry
Chronic villitis of unknown etiology (VUE) occurs in 5% of placentas submitted to pathology and is characterized by lymphohistiocytic infiltration of chorionic villi. VUE is associated with fetal growth restriction, preterm birth, and recurrent pregnancy loss. Accumulating evidence indicates that VUE may represent a host-versus-graft reaction analogous to transplant rejection. Pathologists routinely screen for antibody-mediated rejection in transplant biopsies by immunostaining for C4d, which highlights the recognition of donor cells by the host immune system. Since the hemochorial placenta is bathed in maternal blood, we hypothesized that cases of VUE may show C4d deposition onto villous syncytiotrophoblasts (STB). Chronic villitis was diagnosed in 82 of 1986 (4%) singleton placentas submitted to our department from 2007 through 2011. Forty randomly selected cases were gestational age-matched with 40 negative controls. Patient charts were reviewed and representative placental sections were immunostained for C4d. A positive C4d result was defined as circumferential immunostaining of the STB around at least one villous, or strong staining of fetal endothelial cells in the chorionic plate or stem villi. Our data indicate that VUE usually occurs in the 3rd trimester (37 ± 0.5 weeks) and is associated with significantly reduced placental weight ( P = 0.006). Positive C4d staining of STB was more common in VUE (35/40, 88%) compared with negative controls (2/40, 5%) ( P < 0.0001). It was also more common in multiparous (35/66, 53%) than primiparous (2/14, 14%) women ( P < 0.01). Although the precise mechanism remains to be determined, our data support the hypothesis that VUE may represent host-versus-graft rejection by the mother.